Work Motivation and Organizational Culture Mediating Transformational Leadership on Employee Performance - Gunawan, Arsyad Daiva; Utama, Zahera Mega; Marwan, Jubery (Universitas prof. Dr. Moestopo (Beragama), 2026)
This study examines the influence of transformational leadership on employee performance, with work motivation and organizational culture as mediating variables. The research was conducted to understand the mechanisms through which leadership affects employee performance within organizational settings. A quantitative approach with a cross-sectional research design was employed. Data were collected through a questionnaire distributed to 304 employees, and the analysis was conducted using path analysis and the Sobel test to examine both direct and indirect relationships among variables. The results indicate that transformational leadership significantly influences work motivation and employee performance. Work motivation also has a significant positive effect on employee performance and plays a mediating role in the relationship between transformational leadership and employee performance. However, transformational leadership does not significantly influence organizational culture, and organizational culture does not mediate the relationship between transformational leadership and employee performance. These findings contribute to leadership and organizational behavior literature by demonstrating that the effectiveness of transformational leadership in improving employee performance operates primarily through individual motivational mechanisms rather than through broader organizational culture. Practically, the results suggest that organizations should strengthen leadership practices that enhance employee motivation in order to improve performance outcomes.